CRISPitope: A generic platform to model target antigens for adoptive T cell transfer therapy in mouse tumor models - Effern, Maike; Glodde, Nicole; Bawden, Emma; Liebing, Jana; Hinze, Daniel; Tüting, Thomas; Gebhardt, Thomas; Hölzel, Michael (STAR protocols, 2022)
This protocol details the procedure for CRISPR-assisted insertion of epitopes (CRISPitope), a flexible approach for generating tumor cells expressing model CD8+ T cell epitopes fused to endogenously encoded gene products of choice. CRISPitope-engineered tumor cells can be recognized by T cell receptor-transgenic (TCRtg) CD8+ T cells that are widely used in immunology research. Using mice inoculated with CRISPitope-engineered tumor cells, researchers can investigate how the choice of the target antigen for T cell immunotherapies influences treatment efficacy and resistance mechanisms. For complete details on the use and execution of this protocol, please refer to Effern et al. (2020). [Display omitted] •Genome editing of tumor cells for experimental standardized T cell recognition•Tagging endogenous gene products with model CD8+ T cell epitopes in tumor cells•Assessing T cell responses directed against differentially regulated gene products•Approach allows studying the impact of the target antigen choice on T cell therapy This protocol details the procedure for CRISPR-assisted insertion of epitopes (CRISPitope), a flexible approach for generating tumor cells expressing model CD8+ T cell epitopes fused to endogenously encoded gene products of choice. CRISPitope-engineered tumor cells can be recognized by T cell receptor-transgenic (TCRtg) CD8+ T cells that are widely used in immunology research. Using mice inoculated with CRISPitope-engineered tumor cells, researchers can investigate how the choice of the target antigen for T cell immunotherapies influences treatment efficacy and resistance mechanisms.